The Determinants of Money Arguments between Spouses - Sonya L Britt; Sandra Huston; Dorothy B Durband (Journal of Financial Therapy, 2010)
A commonly held view is that arguments about money are associated with marital problems, but relatively little is known about the nature of arguing about money within marriage. Using data from the National Longitudinal Survey of Youth 1979 (NLSY79), this study uses a collective bargaining approach to examine the role of money arguments in marriage. The sample (N = 1,371) consists of married women. A collective bargaining framework provides a context for understanding money arguments within the marital relationship. Results indicate that costly communication is the dominant predictor of money arguments, followed by level and proportion of wife’s income, and household net worth. Because results suggest that both communication and financial resources are important components to understanding money arguments within marriage, a combination of professionals trained in marital therapy and/or financial planning is required for couples interested in seeking assistance to increase their satisfaction and/or avoid divorce.
Keywords: financial therapy; financial planning; economic theory